Water taxation and the double dividend hypothesis - Kilimani, Nicholas; Heerden, Jan van; Bohlmann, Heinrich (Water Resources and Economics, 2015)
The double dividend hypothesis contends that tax policies which are aimed at protecting the environment can potentially yield other benefits for the economy. However, empirical evidence of the potential impacts of environmental taxation in developing countries is still limited. This may be partly due to the limited use of environmental tax policies in economic and environmental management in many of these countries. This paper seeks to contribute to the literature by exploring the impact of a water tax in a developing country context, with Uganda as a case study. Policy makers in Uganda are exploring ways of raising revenue by taxing environmental goods such as water. Whereas their primary focus is to raise revenue, this study is aimed at demonstrating how taxes on environmental goods can potentially yield other benefits beyond addressing a country's fiscal needs. This study employs a computable general equilibrium model to shed light on the impact of a water tax policy when a tax is accompanied by a plough-back scheme of the same magnitude. We seek to establish whether a water tax policy that is accom- panied by a revenue plough-back scheme can induce more growth, employment and industry output. Whatever the degree of regressivity resulting from the tax, it is possible to design a policy that benefits the economy. The policy was also checked for sustainability using a long-run water demand scenario. The results show that water demand remains more or less on the same trajectory and in fact, a higher level of dividends is realized.
Keywords: Environmental tax; Revenue plough-back; Double dividend; Economic growth